2021
DOI: 10.1186/s12864-021-08045-8
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics provides insights into the population structure and temperature-driven adaptation of Collichthys lucidus

Abstract: Background Understanding the genetic structure and local adaptive evolutionary mechanisms of marine organisms is crucial for the management of biological resources. As the ecologically and commercially important small-sized shallow-sea fish, Collichthys lucidus plays a vital role in the structure and functioning of marine ecosystem processes. C. lucidus has been shown to have an obvious population structure. Therefore, it is an ideal candidate for investigating population differentiation and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Second, two genetic lineages of L. exotica exhibited general allopatric distribution, which appears to be more evident in China along the coastline than in Japan. Similarly, such allopatric distribution patterns have been reported in many diverse marine taxa such as Collichthys lucidus (Richardson, 1844), Cyclina sinensis (Gmelin, 1791), Eriocheir De Haan, 1835, Monodonta labio (Linnaeus, 1758), Oratosquilla oratoria (De Haan, 1844), and Tubaca arcuate (De Haan, 1835) (Xu et al, 2009;Ni et al, 2012;Cheng and Sha, 2017;Zhao et al, 2017;Zhao et al, 2021;Hwang et al, 2022;Shih et al, 2022). Such studies suggested that the allopatric distribution observed in the coastline of China is caused by sea level fluctuations in the Pleistocene (Xu et al, 2009;Ni et al, 2014).…”
Section: Phylogeographical Patterns Of Two Ligia Species In East Asiamentioning
confidence: 55%
“…Second, two genetic lineages of L. exotica exhibited general allopatric distribution, which appears to be more evident in China along the coastline than in Japan. Similarly, such allopatric distribution patterns have been reported in many diverse marine taxa such as Collichthys lucidus (Richardson, 1844), Cyclina sinensis (Gmelin, 1791), Eriocheir De Haan, 1835, Monodonta labio (Linnaeus, 1758), Oratosquilla oratoria (De Haan, 1844), and Tubaca arcuate (De Haan, 1835) (Xu et al, 2009;Ni et al, 2012;Cheng and Sha, 2017;Zhao et al, 2017;Zhao et al, 2021;Hwang et al, 2022;Shih et al, 2022). Such studies suggested that the allopatric distribution observed in the coastline of China is caused by sea level fluctuations in the Pleistocene (Xu et al, 2009;Ni et al, 2014).…”
Section: Phylogeographical Patterns Of Two Ligia Species In East Asiamentioning
confidence: 55%
“…In addition, a novel genetic cluster comprising populations in the Lake Biwa drainage was identified, likely due to the time resolution of the methods employed for the investigation of genetic structures and sample sites. NGS‐based genome‐wide SNP analyses generally have finer resolution than conventional haplotype analyses for mitochondrial DNA (Hirai, 2020; Zhao et al, 2021). In addition, genome‐wide analyses avoid accidental biases, such as mitochondrial replacement or selective sweeps (Christie & Beekman, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Spinyhead croaker, Collichthys lucidus , is a small shallow‐water fish with a short‐distance migratory habit, mainly distributed in the west coast of the Pacific Ocean, from Japan to the Philippines (Zhao et al ., 2021). It is a potential cultured species being exploited due to its delicious taste and high economic value.…”
Section: Introductionmentioning
confidence: 99%